Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1757913916634136
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient satisfaction: a systematic review

Abstract: Health care service quality indicators were the most influential determinants of patient satisfaction across the studies. Among them, health providers' interpersonal care quality was the essential determinant of patient satisfaction. Sociodemographic characteristics were the most varied in the review. The strength and directions of associations with patient satisfaction were found inconsistent. Therefore, person-related characteristics should be considered to be the potential determinants and confounders simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
608
8
39

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(716 citation statements)
references
References 132 publications
(966 reference statements)
61
608
8
39
Order By: Relevance
“…This is in accordance with the opinion expressed by Batbaatar et al (2016) that the indicator of the quality of health services has a strong and positive influence on patient satisfaction. The same opinion is expressed by Lankarani et al (2016) which states that patient satisfaction is an indicator of service quality and efficiency of health services.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the opinion expressed by Batbaatar et al (2016) that the indicator of the quality of health services has a strong and positive influence on patient satisfaction. The same opinion is expressed by Lankarani et al (2016) which states that patient satisfaction is an indicator of service quality and efficiency of health services.…”
supporting
confidence: 92%
“…The more frequent the frequency of patients visiting a community health center the higher the level of satisfaction (Batbaatar et al, 2016). While Birhanu et al, (2010) stated that patients who frequently visit community health centers will have good relations with officials.…”
Section: Factors Affecting To Quality Ofmentioning
confidence: 99%
“…Quality of health communication, willingness to pay high treatment costs, being married, being young and having experience in taking care of patients-these are factors that could increase positivity in patient attitude towards health care services, which is in line with recent empirical findings on determinants of patient satisfaction [35]. Of these factors, health communication and marital status are the most influential.…”
Section: Discussionsupporting
confidence: 69%
“…7 In particular, this review found that interpersonal care and affective behaviors such as respect and courtesy in interactions with nurses and physicians had effects on patients' satisfaction with their care. However, there was inconsistent evidence about the relationships between patients' demographic and psychological characteristics and their overall satisfaction.…”
Section: Bartlett Ellis Et Almentioning
confidence: 98%